ESSENCE AND TYPES OF FINANCIAL RECOVERY OF BANKS: THEORETICAL ASPECTS - Стаднійчук, Роман (Socio-economic relations in the digital society, 2019)
The article reveals the essence of fi nancial rehabilitation of banks, its role in strengthening their sustainability and emerging from crisis situations. Th e measures aimed at improving the financial status of banks are substantiated. The approaches to the defi nition of «fi nancial healing» of the banking institution, which are found in the economic literature, are determined. It is proposed to treat the financial healing of the bank in a broad and narrow sense. In the first case, financial recovery is characterized by stabilization of the financial condition of the bank, caused by the structural elements of crisis phenomena, based on the application of financial management techniques and technologies by changing its policy of asset and liability management of the bank. In the second case, financial rehabilitation is a strategic vision, a strategic set of measures aimed not only at eliminating the immediate causes of the crisis at one stage or another of the life cycle of the banking institution, but also to neutralize the factors that worsen the financial, economic and economic conditions of the bank. Attention is paid to the legislative interpretation of the bank’s financial rehabilitation — as the restoration of the bank’s solvency and the bringing of financial indicators of its activities in line with the requirements of the National Bank of Ukraine. It is proposed to fi nancially improve the bank to understand the improvement of financial and economic indicators, increase the market value of the banking institution, increase its level of capitalization. Three main types of fi nancial rehabilitation of banks are described, including preventive financial rehabilitation, fi nancial recovery in the conditions of the crisis, post-crisis financial rehabilitation. The basic measures of financial rehabilitation of the bank are developed.